2020
DOI: 10.1038/s41467-020-18956-x
|View full text |Cite
|
Sign up to set email alerts
|

Synapse type-specific proteomic dissection identifies IgSF8 as a hippocampal CA3 microcircuit organizer

Abstract: Excitatory and inhibitory neurons are connected into microcircuits that generate circuit output. Central in the hippocampal CA3 microcircuit is the mossy fiber (MF) synapse, which provides powerful direct excitatory input and indirect feedforward inhibition to CA3 pyramidal neurons. Here, we dissect its cell-surface protein (CSP) composition to discover novel regulators of MF synaptic connectivity. Proteomic profiling of isolated MF synaptosomes uncovers a rich CSP composition, including many CSPs without syna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 129 publications
1
34
0
Order By: Relevance
“…This notion is especially of interest in the study of connectivity between neurons and more generally the organization of the nervous system, as CSP patterning could hold key information on how and where two brain cells connect. This was demonstrated in a recent article by Apóstolo et al (52). In this study, mossy fiber synaptosomes were isolated via sucrose gradient centrifugation, making use of the mossy fiber characteristically large in size, where a large presynaptic bouton engulfs a series of postsynaptic densities or multiheaded dendritic spines.…”
Section: Neurocytometry -mentioning
confidence: 84%
“…This notion is especially of interest in the study of connectivity between neurons and more generally the organization of the nervous system, as CSP patterning could hold key information on how and where two brain cells connect. This was demonstrated in a recent article by Apóstolo et al (52). In this study, mossy fiber synaptosomes were isolated via sucrose gradient centrifugation, making use of the mossy fiber characteristically large in size, where a large presynaptic bouton engulfs a series of postsynaptic densities or multiheaded dendritic spines.…”
Section: Neurocytometry -mentioning
confidence: 84%
“…Because Kirrel3 was previously reported to participate in the formation of Mf filopodia to GABAergic neuron synapses ( 42 ) and IgSF8 was more recently reported to be involved in maintaining MF boutons and filopodial density ( 44 ), we assessed whether loss of LRRTM3 also affects connections at these particular synapses. Close examination of the presynaptic filopodia from the reconstructed MfBs showed that each individual MfB in adult WT mice possesses approximately two presynaptic filopodia, as previously reported ( 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…LRRTM3 is dispensable for development of Mf filopodia–CA3 pyramidal neuron synapses, although the proportion of these synapses was much lower (∼0.9%) in juvenile postnatal day (P)42 WT and Lrrtm3 -KO mice than in P14 WT mice (∼5.2%) ( 42 ). These data suggest that different sets of cell-surface proteins are involved in organizing the structural projections of DG Mf to distinct postsynaptic targets (i.e., LRRTM3 targeting CA3 pyramidal neurons, Kirrel3 targeting GABAergic interneurons, and IgSF8 targeting DG, CA3, and GABAergic interneurons) ( 33 , 44 ). The number of Mf filopodia was significantly higher in Lrrtm3 -KO mice than in WT mice, although there was no difference in the length of their Mf filopodia.…”
Section: Discussionmentioning
confidence: 96%
“…Despite these difficulties, methods such as projection-specific barcoding and profiling of growth cones are being developed that enable unbiased and high-throughput analyses of candidate molecular mechanisms for cortical synaptic targeting (Biesemann et al, 2014;Poulopoulos et al, 2019;Apostolo et al, 2020;Sun et al, 2021). Furthermore, proximity-based labeling methods such as APEX and BioID can be used to specifically tag proteins in the synapses of cell populations of interest, allowing for cell-type and domain-specific profiling of candidate molecules (Loh et al, 2016;Spence et al, 2019;Li et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%